Calculations of Electron Capture Cross-Sections of Mg Atoms due to Proton, 3He+ and 3He2+ Ions Impact (Bulletin of Pure and Applied Sciences – Physics, 2020)
Proton, 3He+ and 3He2+ ions impact Electron Capture Cross sections for Mg atoms  have been calculated in the Modified Binary Encounter Approximation. The Hartree  Fock Velocity distribution for the target electrons has been used throughout the  calculations. The effect of angular divergence as correction factor has also been taken  into account. The present calculations show fairly good agreement with the  experimental observations.